Assessing Students' Readiness to Implement Business and Professional Ethics in the Workplace - Yusup Hari Subagya; Poniman; Darmanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study investigates students' readiness to implement business and professional ethics in the workplace and identifies the factors that influence such readiness. The study employed a descriptive quantitative approach involving 42 sixth-semester students from the Diploma III programs in English, Accounting, and Financial Management at Pignatelli Triputra University. The participants had completed Business Ethics and Professional Ethics courses and had undertaken internship programs. Data were collected using a five-point Likert-scale questionnaire and analyzed through descriptive statistical techniques and thematic analysis. The findings reveal that students demonstrate a high level of readiness to apply ethical principles in professional settings, with an overall mean score of 4.45 out of 5. Ethical attitude emerged as the most influential factor (4.66), followed by ethical knowledge (4.45), internship experience (4.43), and the campus environment (4.18). In addition, students expressed highly positive perceptions regarding the importance of ethics in professional life. The major challenges identified include work pressure, conflicts of interest, unethical organizational environments, and temptations to engage in dishonest practices. The study concludes that students' readiness to implement business and professional ethics is shaped by cognitive, affective, and experiential dimensions that are reinforced by an institutional culture promoting integrity. Therefore, higher education institutions should strengthen ethics-based education, expand experiential learning opportunities, and cultivate an academic culture of integrity to better prepare graduates for ethical challenges in the workplace. Keywords: business ethics, professional ethics, work readiness, integrity, higher education.